Pengaruh Likuiditas, Struktur Modal dan Manajemen Aset terhadap Kinerja Keuangan pada Perusahaan Transportasi dan Logistik yang Terdaftar di Index Saham Syariah Indonesia (ISSI) - Ade Khairani Hasibuan; Zulfa Khairina Batubara (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines the influence of liquidity, capital structure, and asset management on the financial performance of transportation and logistics companies listed on the Indonesian Sharia Stock Index (ISSI). The main issue addressed is the inconsistency between theoretical expectations and empirical conditions, where changes in financial ratios do not always align with profitability trends. This research aims to analyze both the simultaneous and partial effects of these variables on financial performance. A quantitative approach was employed using secondary data from annual financial reports over the 2022-2024 period. The sample consisted of 11 companies selected through purposive sampling, resulting in 33 observations. Data were analyzed using multiple linear regression, supported by classical assumption tests and hypothesis testing. The findings indicate that liquidity, capital structure, and asset management do not simultaneously have a significant effect on financial performance. Partially, liquidity and capital structure show no significant effect, while asset management has a positive and significant influence. These results suggest that efficient utilization of assets plays a more important role in improving financial performance than short-term liquidity or capital structure decisions.